An aberrant precision account of autism - Lawson, Rebecca P.; Rees, Geraint; Friston, Karl J. (Frontiers in Human Neuroscience, 2014)
Autism is a neurodevelopmental disorder characterised by problems with social-communication, restricted interests and repetitive behaviour. A recent and controversial article presented a compelling normative explanation for the perceptual symptoms of autism in terms of a failure of Bayesian inference (Pellicano and Burr, 2012). In response, we suggested that when Bayesian interference is grounded in its neural instantiation – namely, predictive coding – many features of autistic perception can be attributed to aberrant precision (or beliefs about precision) within the context of hierarchical message passing in the brain (Friston et al., 2013). Here, we unpack the aberrant precision account of autism. Specifically, we consider how empirical findings – that speak directly or indirectly to neurobiological mechanisms – are consistent with the aberrant encoding of precision in autism; in particular, an imbalance of the precision ascribed to sensory evidence relative to prior beliefs.